Hybrid civil society organizations in Vietnam: the case of the fishery union of Quang Ngai province - Huynh Ngoc Le; Nguyen Bang Nong; Ha Tham Thu Nguyen (Otoritas : Jurnal Ilmu Pemerintahan, 2025)
The universal application of the traditional social work model has faced growing criticism in non-Western contexts, particularly in developing countries like Vietnam and China, where the relationship between the state and social organizations is complex and multifaceted. This study addresses this gap by examining the Fisheries Trade Union in Quang Ngai province as a representative example of a hybrid civil society actor in Vietnam. Using a qualitative ethnographic approach, which includes fieldwork and organizational analysis, we explore how the Union navigates its dual role as both a conduit for implementing state policies and an advocate for its members' negotiations to gain autonomy, despite significant institutional constraints. The study presents a novel model of organizational resilience and community empowerment that challenges the conventional state-society dichotomy prevalent in Western theories. This study uses ethnographic approach in over six months in 2024, with a combination of semi-structured interviews, focus group discussions, document analysis, and participant observation. This research contributes to a deeper understanding of hybrid organizational structures in non-Western settings, offering novel insights into their potential for fostering community-based social development and providing a more nuanced perspective for both researchers and policymakers. Qualitative analysis demonstrates that the Union sustains and advances itself by strategically balancing dual functions: executing state policy directives while representing and safeguarding the interests of the fishing community.